Oral and Dermal Candidiasis Among Infants in Al-Battol Teaching Hospital - H Khaleefa, Raghad; T Ahmed, Luma; S Hameed, Dawood (Diyala Journal of Medicine, 2020)
Background: Candida spp. is the yeast caused infection termed candidiasis; this is naturally found on the skin and inner the body, in an area like the gut, intestines, throat, vagina, and mouth, with the absence inciting any problems. Candida albicans is yeast naturally found in the skin; intestinal tract; vaginal and mouth. This is a polymorphic yeast (that capable of growing either as avoid shaped budding yeast, when it affect the mouth, it is typically termed oral thrush, and when it affect the dermal (diaper area) called diaper rash. clinical signs and symptoms involve white patches on the or other areas of the mouth and throat, `other signs may involve soreness and problems of swallowing. Objective: To study detection, isolation, and identification of C. albicans from infants in Al-Battol Teaching Hospital in Diyala Province by routine laboratory procedure, and identification of other species of Candida. Patients and Methods: Two hundred samples were taken from infants less than 2 years who attended Al-Battol teaching Hospital in Diyala, province during the period from October 2019 to February 2020. Method of this study by making a routine and confirmative diagnosis processes involve a microscopic examination, culture on Sabouraud’s dextrose agar for diagnosis of primary invasive candidiasis, and culture on chrome agar for differentiating between C. albicans and other spp. Results: The results of this study showed the isolates of oral samples were 12 (24%) C. albicans and 18(36.0%) C. non albicans; for dermal isolates were 10(20.0%) C. albicans and 17(34.0%) C. non albicans; and for both isolates oral and dermal samples were 13(26.0%) C. albicans and 21 (42.0) C. non albicans. Conclusion: In this study found that the male are more infected by Candida than female. And also we concluded that small age children more infected than large age.